THE EFFECT OF SCHOOL FACILITIES AND SOCIAL SCIENCES TEACHER PERFORMANCE ON STUDENT LEARNING ACHIEVEMENT IN SOCIAL SCIENCES AT STATE MIDDLE SCHOOL 2 BOSAR MALIGAS - Recha Riski Simaremare; Sotarduga Sihombing; Herlina Htmadinar Sianipar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of school facilities and teacher performance on student achievement in social studies for eighth graders at SMP Negeri 2 Bosar Maligas in the 2024/2025 academic year. Student achievement in this study is examined from a cognitive perspective, specifically the Mid-Semester Exam (UTS) scores for social studies. The research method used was a quantitative approach with a descriptive approach. The study population was all 67 eighth grade students, using a saturated sampling technique, thus sampling the entire population. Data collection instruments included questionnaires and documentation of mid-term exam scores. Data analysis used multiple linear regression with partial (t-test) and simultaneous (F-test) tests. The results showed that (1) school facilities had a positive and significant effect on social studies achievement for eighth graders at SMP Negeri 2 Bosar Maligas; (2) teacher performance had a positive and significant effect on social studies achievement; and (3) school facilities and teacher performance simultaneously had a significant effect on social studies achievement. Thus, it can be concluded that improving the quality of school facilities and optimizing teacher performance are important factors in efforts to improve student learning achievement.